2022
DOI: 10.1002/micr.30862
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of risk factors for complications of perforator propeller flaps used for soft tissue reconstruction after malignant tumor resection: A systematic review and meta‐analysis

Abstract: Background: Perforator propeller flaps (PPFs) have been widely used due to their numerous advantages; however, they were also associated with various complications. Herein, we analyzed the risk factors for complications of PPFs used for soft tissue reconstruction after malignant tumor resection. Methods:We searched databases for articles on soft tissue reconstruction using PPFs after malignant tumor resection published between January 1991 and April 2021. Studies were selected according to the preferred report… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
4
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 47 publications
0
4
1
Order By: Relevance
“…One of the venous congestive flaps progressed to necrosis, which could be attributed to the perforator damage, and finally, a secondary skin graft was performed for repair. A meta‐analysis reported that age ≥60 years, smoking, diabetes, and radiotherapy are the risk factors associated with complications in flap reconstruction 22 . Herein, we did not find any risk factors for complications due to the low complication rate (6.6%).…”
Section: Discussioncontrasting
confidence: 51%
See 2 more Smart Citations
“…One of the venous congestive flaps progressed to necrosis, which could be attributed to the perforator damage, and finally, a secondary skin graft was performed for repair. A meta‐analysis reported that age ≥60 years, smoking, diabetes, and radiotherapy are the risk factors associated with complications in flap reconstruction 22 . Herein, we did not find any risk factors for complications due to the low complication rate (6.6%).…”
Section: Discussioncontrasting
confidence: 51%
“…19 The application of a nasolabial perforator flap makes primary surgery available. About 65.5% of defects in this study have The common postoperative complications of perforator flaps include venous congestion and partial necrosis, 22 and the former occurred in 4.9% of flaps in the present study. One of the venous congestive flaps progressed to necrosis, which could be attributed to the perforator damage, and finally, a secondary skin graft was performed for repair.…”
Section: Discussionmentioning
confidence: 51%
See 1 more Smart Citation
“…Flap complications most commonly result from vascular insufficiency and, given the small diameter and length of the perforators in SCIP flaps, expertise in perforator dissection is vital to avoid venous congestion on flap inset or inadvertent perforator arterial injury. 6,7 Higher wound complication rates have been reported in smokers, diabetics, patients over the age of 60 years and recipients of pre-operative radiotherapy. 7 Our patients' only risk factor was her neoadjuvant radiotherapy and when planning SCIP procedures the individuals risk profile should be carefully considered.…”
Section: Discussionmentioning
confidence: 99%
“…6,7 Higher wound complication rates have been reported in smokers, diabetics, patients over the age of 60 years and recipients of pre-operative radiotherapy. 7 Our patients' only risk factor was her neoadjuvant radiotherapy and when planning SCIP procedures the individuals risk profile should be carefully considered.…”
Section: Discussionmentioning
confidence: 99%